RNA shotgun metagenomic sequencing of northern California (USA) mosquitoes uncovers viruses, bacteria, and fungi - Chandler, James Angus; Liu, Rachel M.; Bennett, Shannon N. (Frontiers in Microbiology, 2015)
Mosquitoes, most often recognized for the microbial agents of disease they may carry, harbor diverse microbial communities that include viruses, bacteria, and fungi, collectively called the microbiota. The composition of the microbiota can directly and indirectly affect disease transmission through microbial interactions that could be revealed by its characterization in natural populations of mosquitoes. Furthermore, the use of shotgun metagenomic sequencing (SMS) approaches could allow the discovery of unknown members of the microbiota. In this study, we use RNA SMS to characterize the microbiota of seven individual mosquitoes (species include Culex pipiens, Culiseta incidens, and Ochlerotatus sierrensis) collected from a variety of habitats in California, USA. Sequencing was performed on the Illumina HiSeq platform and the resulting sequences were quality-checked and assembled into contigs using the A5 pipeline. Sequences related to single stranded RNA viruses of the Bunyaviridae and Rhabdoviridae were uncovered, along with an unclassified genus of double-stranded RNA viruses. Phylogenetic analysis finds that in all three cases, the closest relatives of the identified viral sequences are other mosquito-associated viruses, suggesting widespread host-group specificity among disparate viral taxa. Interestingly, we identified a Narnavirus of fungi, also reported elsewhere in mosquitoes, that potentially demonstrates a nested host-parasite association between virus, fungi, and mosquito. Sequences related to 8 bacterial families and 13 fungal families were found across the seven samples. Bacillus and Escherichia/Shigella were identified in all samples and Wolbachia was identified in all Cx. pipiens samples, while no single fungal genus was found in more than two samples. This study exemplifies the utility of RNA SMS in the characterization of the natural microbiota of mosquitoes and, in particular, the value of identifying all microbes associated with a specific host.